The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jmwh.13186
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Related Factors, and Levels of Burnout Among Midwives: A Systematic Review

Abstract: Introduction Burnout refers to a constellation of feelings of exhaustion, depersonalization, and low sense of personal accomplishment that develops secondary to long‐term occupational stress. Several studies have identified that health care professionals are a high‐risk occupational group for burnout, but knowledge about this syndrome among midwives has not been fully explored. The purpose of this study was to perform a systematic review of the prevalence and levels of burnout among midwives and analyze the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 69 publications
2
26
0
4
Order By: Relevance
“…Most studies measuring burnout among midwives have been conducted in caseload and non-caseload models of care in Australia, Scandinavia, the United Kingdom, Japan, Spain, or Turkey 8 - 10 . However, there are substantial differences in midwifery practice, between and within countries, with respect to the role and responsibilities of midwives, midwifery education, organization, and care models 2 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies measuring burnout among midwives have been conducted in caseload and non-caseload models of care in Australia, Scandinavia, the United Kingdom, Japan, Spain, or Turkey 8 - 10 . However, there are substantial differences in midwifery practice, between and within countries, with respect to the role and responsibilities of midwives, midwifery education, organization, and care models 2 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…During this process, midwives also face additional challenges of frustration due to their increased workload and poor communication with the psychiatrist, as well as noncompliance of the mothers due to stigma surrounding mental health and poor hospital conditions. High workload, poor relationships with supervisors, and perceived lack of time to provide high quality care for patients are all risk factors for burnout among midwives worldwide [3]. However, in this study, midwives reported they are satisfied with the current system, and mostly made minor suggestions for improvement, such as integrating a depression screening questionnaire to the antenatal care protocol.…”
Section: Discussionmentioning
confidence: 64%
“…We as midwives do more frequent home visits to ensure her compliance, to make sure she takes her medications at the correct time, to check her improvement and to educate the family members and gain their support. We also visit them along with the psychiatrist when we check her improvement to decide on further treatments.-PHM 3 We talk with the patient as well as with the family members spending a lot of time with them. We advise the family on how to take care of a mother with such a problem.…”
Section: Sometimes They Are Not Attending To Household Work Like Earl...mentioning
confidence: 99%
See 1 more Smart Citation
“…44 In contrast, excessive workload and an ongoing lack of resources can be expected to increase burnout, which results in high rates of turnover and leaving health professions. [45][46][47] A more flexible workforce could facilitate care practices that reduce risk of transmission such as expansion of telehealth services, early hospital discharge with postpartum home care, and home visits for newborn well checks. Increasing flexibility will require a range of changes in training, employment, practice, and reimbursement.…”
Section: Discussionmentioning
confidence: 99%